Esterification of Crude Palm Oil Using H2SO4 and Transesterification Using CaO Catalyst Derived from Anadara granosa - Nurhayati Nurhayati; Sofia Anita; Tengku Ariful Amri; Amilia Linggawati (Universitas Gadjah Mada, 2017)
In this study biodiesel was produced from crude palm oil through two-step processes, namely esterification reactions using homogeneous H2SO4 catalyst and transesterification using the heterogeneous base CaO catalyst derived from Anadara granosa shell. Several parameters affecting to the yields of biodiesel were investigated including the amount of the catalysts, the molar ratios of oil to methanol, reaction times and reaction temperatures. The CaO catalyst was prepared by calcining the A. granosa shells at the temperatures of 800 and 900 °C for 10 h. The as-synthesized biodiesel was analyzed using GC and its characteristics were determined and the results were compared to Standard National for Biodiesel (SNI 04-7183-2006). The optimum condition for the esterification process (step 1) was as follows: reaction temperature of 65 °C, reaction time of 3 h and mol ratio of oil to methanol 1:24. For the transesterification (step 2) the optimum conditions were attained using the catalyst weight 3%, reaction temperature of 60 °C, reaction time of 3 h, mole ratio of oil/methanol 1:6 and the catalyst calcination time of 10 h with the conversion of 87.17%. This biodiesel yield by the two-step processes was higher (2.7%) than that using only one-step process (transesterification).